Jawi character recognition using the trace transform - Mohammad Faidzul Nasrudin; Khairuddin Omar; Mohamad Shanudin Zakaria (Universiti Kebangsaan Malaysia, 2010)
The Trace transform, a generalisation of the Radon transform, allows one to construct image features that are invariant to a chosen group of image transformations. In this paper, we used some features, which are invariant to affine distortion, generated by the Trace transform to discriminate between Jawi characters. The process consists of tracing an image with straight lines, along which certain functionals of the image function are calculated, in all possible orientations. For each combination of functionals we derived a function of orientation of the tracing lines that is known as an object signature. If the functionals used have some predefined properties, this signature can be used to characterise the character in an affine way. We demonstrated the usefulness of the derived signature and compared the result of character recognition with those obtained by using features based on affine moment invariants. Experiments using the Trace transform produced decent results for the printed and handwritten Jawi character recognitions that are invariant to affine distortion.Keyword: Affine moment invariant; Jawi character recognition; trace transform